Do locked compression intramedullary nails improve the biomechanical stability of distal femoral fractures? - Wild, Michael; Thelen, Simon; Spoor, Vera; Eichler, Christian; Koebke, Juergen; Jungbluth, Pascal; Betsch, Marcel; Windolf, Joachim; Hakimi, Mohssen (Journal of Trauma-Injury Infection and Critical Care, 2011)
Background: A distal femur nail with fixed-angle locking screws intends to combine the advantages of angular stability and intramedullary stabilization in extraarticular distal femur fractures. The goal of this study was to analyze whether the locked compression distal femur nail (LCN) was biomechanically more stable than a conventional standard distal femur nail (CN). Methods: Both nails were compared on a series of 10 matched pairs of human femora. After setting a distal femur defect fracture, the intramedullary stabilized femur was axially loaded starting from 100 N, increasing in steps of 100 N after every 200 cycles with a triangular frequency of 1 Hz, until a predefined point of failure was reached. Results: The two types of nails showed no significant difference in terms of maximum tolerated load, maximum number of cycles repeated, or axial deformation of the bone-implant construct. The mean load at failure was 2,954 N for the CN and 2,483 N for the LCN. The mean axial deformation for the conventional (14.8 mm) and locked compression nail (15.3 mm) did not differ significantly. Mode of failure was a bony fracture in all specimens predominantly involving the proximal femur. Conclusion: No significant difference in stability between the two compared implants could be demonstrated. The LCN showed comparable characteristics under cyclic axial loading as the conventional distal femur nail. No migration into the articular space or implant failure was observed. Copyright © 2011 by Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Biomechanical testing; Extraarticular distal femur fractures; Fixed angle; Intramedullary nails; Locked compression